Interdisciplinary project-based learning at master level: control of robotic mechatronic systems. Issue 6 (2016) - Copot, Cosmin; Ionescu, Clara; Keyser, Robin De
Abstract: This paper presents a project based learning at master level with strong interdisciplinary elements. Within the course of ICT and Mechatronics at Ghent University, the classical laboratory experiments do not present a suitable challenge for the students. In order to motivate them and rise their interest in the field, challenging smaller projects (i.e. control of a mechatronic system) are introduced in the curriculum. During the projects, the students have to use their skills such as programming languages (e.g. C++, Java etc.), communication, basic control techniques, etc. As an outcome, the students acquire the appropriate competences (e.g. ability to understand a mechatronic system, a motion control strategy, etc.) needed to deal with this kind of problems at industrial level.